Nonclinical safety, tolerance and pharmacodynamics evaluation for meplazumab treating chloroquine-resistant Plasmodium falciparum - Kun Zhang; Yu Zhao; Zheng Zhang; Mengyao Zhang; Xiaodong Wu; Huijie Bian; Ping Zhu; Zhinan Chen (Acta Pharmaceutica Sinica B, 2020)
Meplazumab is an anti-CD147 humanized IgG2 antibody. The purpose of this study was to characterize the nonclinical safety, tolerance and efficacy evaluation of meplazumab treating chloroquine resistant Plasmodium falciparum. Meplazumab was well tolerated in repeat-dose toxicology studies in cynomolgus monkeys. No observed adverse effect level was 12 mg/kg. No difference between genders in the primary toxicokinetic parameters after repeat intravenous injection of meplazumab. No increased levels of drug exposure and drug accumulation were observed in different gender and dose groups. Meplazumab had a low cross-reactivity rate in various tissues and did not cause hemolysis or aggregation of red blood cells. The biodistribution and excretion results indicated that meplazumab was mainly distributed in the plasma, whole blood, and hemocytes, and excreted in the urine. Moreover, meplazumab effectively inhibited the parasites from invading erythrocytes in humanized mice in a time-dependent manner and the efficacy is superior to that of chloroquine. All these studies suggested that meplazumab is safe and well tolerated in cynomolgus monkeys, and effectively inhibits P. falciparum from invading into human red blood cells. These nonclinical data facilitated the initiation of an ongoing clinical trial of meplazumab for antimalarial therapy.